2021
DOI: 10.1111/and.13989
|View full text |Cite
|
Sign up to set email alerts
|

The current perspective on genetic and epigenetic factors in sperm maturation in the epididymis

Abstract: Male infertility affects approximately 30% of infertile couples. As spermatozoa mature in the epididymal lumen, their potential for mobility increases, and their protein, lipid and small RNA (sRNA) content changes, whereas capacitation and fertilisation take place in the female reproductive tract. Both of the latter processes are affected by maturation, because impaired maturation causes premature capacitation and fertilization. The epididymis produces a suitable environment for sperm maturation via ion transp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 70 publications
0
19
0
Order By: Relevance
“…Globally, the transcriptome increases and undergoes dramatic transformations [ 10 ]. For that reason, in the head and in the tail of the epididymis, the spermatozoa transcriptome shows different compositions [ 8 , 9 ]. The most prominent changes are the reduction of piRNAs, the increase of the tsRNAs, and the increase and diversification of the miRNAs [ 10 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Globally, the transcriptome increases and undergoes dramatic transformations [ 10 ]. For that reason, in the head and in the tail of the epididymis, the spermatozoa transcriptome shows different compositions [ 8 , 9 ]. The most prominent changes are the reduction of piRNAs, the increase of the tsRNAs, and the increase and diversification of the miRNAs [ 10 ].…”
Section: Resultsmentioning
confidence: 99%
“…The most prominent changes are the reduction of piRNAs, the increase of the tsRNAs, and the increase and diversification of the miRNAs [ 10 ]. Proteome, in turn, seems to have an important influence on the induction of latency and potential capabilities [ 9 ]. Some RNAs and proteins remain in the seminal fluid performing their roles [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When the sperm sample is retrieved by testicular aspiration (TESE) [ 73 ] or epididymal aspiration (MESA) [ 74 ], the spermatozoa might appear immotile due to the lack of complete maturation that takes place in the final tract of the epididymis [ 75 ].…”
Section: Advanced Methodsmentioning
confidence: 99%
“…Previously, the sperm epigenome was not of significant importance, as it was thought that, after fertilization, all epigenetic marks were erased. However, with the passing of the years and the advancement of science, studies have increasingly demonstrated that epigenetic information carried by spermatozoa can indeed be transmitted between generations [ 98 , 99 , 100 , 101 , 102 ].…”
Section: Diet and Male Reproductive Epigeneticsmentioning
confidence: 99%